2017
DOI: 10.1080/14616688.2017.1417472
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging physical and digital liminoidal spaces: the case of the #EATCambridge festival

Abstract: This paper conceptualises the way physical and digital spaces associated with festivals are being harnessed to create new spaces of consumption. It focuses on the ways local food businesses leverage opportunities in the tourist-historic city of Cambridge. Data from a survey of 28 food producers (in 2014) followed by 35 in-depth interviews at the EAT Cambridge food festival (in 2015) are used to explain how local producers overcome the challenges of physical peripherality and why they use social media to help s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…The three studies on the effects of digital technologies on tourism explored how social media, blogs and Augmented Reality Apps can attract tourists and improve their experiences [42,44,48]. All three solutions were proved key in local promotion strategies, as able to tell a story and involve tourists emotionally.…”
Section: Research Studies Fields and Aimsmentioning
confidence: 99%
“…The three studies on the effects of digital technologies on tourism explored how social media, blogs and Augmented Reality Apps can attract tourists and improve their experiences [42,44,48]. All three solutions were proved key in local promotion strategies, as able to tell a story and involve tourists emotionally.…”
Section: Research Studies Fields and Aimsmentioning
confidence: 99%
“…The festival houses approximately 55 traders, lasting for two full weeks, inclusive of over 40 different fringe events and two main “event days” in the city centre (EAT Cambridge, 2017). Primary data were generated through a non-probability purposive sampling method (Yin, 2013), directly targeting participating micro and small producers and key informants across the food and drink community directly involved with the festival – a similar approach to both Blichfeldt and Halkier (2014) and Duignan et al (2017). In total, 17 open-ended survey data responses (2014) were collected from producers and ten in-depth semi-structured interviews (2015) based on initial themes from 2014 were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, Quinn (2006) has found that festivals have a social and cultural significance far beyond short-term income generation. These discourses highlight the shift away from everyday neoliberal forms of corporate consumption toward a more alternative, locally-focused mode of critical consumption (Sassatelli and Davolio, 2010;Duignan, Everett, Walsh and Cade, 2017).…”
Section: Grassroots (Food) Festivals and The Rise Of Alternative Spacmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed across the Analysis section, this article reveals that for locals, London’s legacy represents an invisible, cancerous inhabitant - a fait accompli with little to no panacea to resist what is perceived to be inevitable displacement of small independent businesses, and the on-going corporatisation and homogenisation of local place and diversity of the high street offer that follows. Throughout, this paper argues that sports mega-events (SME) (legacies) often fail to recognise the critical role local communities play in collectively contributing to local identity and strengthening the cultural offer (Hawkins and Ryan, 2013; Duignan et al , 2017; Maheshwari et al , 2011). And although events and the portfolio of activities that derive from such event-led urban policy often (ideally) play a part in constructing a more holistic destination development (Richards, 2017), through both a mixture of bottom-up community and top-down cultural programming (Christou, 2017) – findings from this article contrast such view.…”
Section: Problematising London’s Olympic Legacymentioning
confidence: 99%